PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, BEBAN KERJA DAN DISIPLIN TERHADAP KINERJA GURU SMA MUHAMMADIYAH 1 GRESIK - Erni Purwanti (Jurnal Manajerial, 2019)
This study aims to examine the influence of Organizational Culture, Work Environment, Workload and Discipline on Teacher Performance of Muhammadiyah Gresik High School. Then a literature review and hypotheses are carried out, as well as data obtained from questionnaires to 55 Muhammadiyah 1 Gresik High School Teachers using Total techniques. Sampling. Testing is done using multiple linear regression analysis. The results of the analysis show that organizational culture has a significant effect on teacher performance variables, the work environment has no effect on teacher performance variables, workload has a significant effect on teacher performance variables, discipline has a significant effect on teacher performance variables.